2021
DOI: 10.3892/mmr.2021.12007
|View full text |Cite
|
Sign up to set email alerts
|

miR‑122‑5p suppresses the oncogenesis of PTC by inhibiting DUSP4 expression

Abstract: MicroRNAs (miRNAs or miRs) play an important role in regulating the occurrence and development of papillary thyroid carcinoma (PTC). miR-122-5p is widely considered a tumour inhibitor, which has not been fully explored in PTC. Bioinformatics analysis identified dual specificity phosphatase 4 (DUSP4), a tumour promoter gene for PTC, as a downstream target of miR-122-5p. The aim of the present study was to investigate the role and molecular mechanism of miR-122-5p in PTC oncogenesis. In this study, the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…DUSP4 is considered a biomarker in various cancer studies, but its precise role is controversial. Previous studies have been performed mainly on breast cancer [19][20][21][22], colorectal cancer [23][24][25][26], lung cancer [27,28], and thyroid papillary carcinoma [12,13,29,30]. Many studies reported that DUSP4 showed an oncogenic effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DUSP4 is considered a biomarker in various cancer studies, but its precise role is controversial. Previous studies have been performed mainly on breast cancer [19][20][21][22], colorectal cancer [23][24][25][26], lung cancer [27,28], and thyroid papillary carcinoma [12,13,29,30]. Many studies reported that DUSP4 showed an oncogenic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many studies on dysregulated DUSP4 expression and cancer have been performed. In several types of cancer, DUSP4 expression affects carcinogenesis and drug resistance; thus, DUSP4 is considered a candidate prognostic marker or therapeutic target [10][11][12][13]. However, its exact molecular mechanism and clinicopathologic role in cancer are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Its underexpression promotes PTC progression [ 54 ]. A study that was recently performed by Hu et al has found that miR-122-5p, through dual specificity phosphatase 4 (DUSP4) inhibition, suppresses PTC oncogenesis [ 55 ] ( Table 2 ).…”
Section: Ptc Mirna-mediated Regulation Of Gene Transcriptionmentioning
confidence: 99%
“…On the other hand, SOX2OT contains a binding site for miR-204 and acts as a sponge for this miRNA ( 11 ). Similarly, some studies have reported that miR-132 and miR-122 have tumor suppressor roles in PTC by suppressing FOXA1 and DUSP4 expression, respectively ( 35 , 36 ). SOX2OT binds to these two miRNAs and suppresses their expression ( 11 ).…”
Section: Discussionmentioning
confidence: 94%